THE PROBLEM OF MIGRATION OF YOUTH OF MONOTOWNS - Irina N. Bogdanova; Khaniya R. Kadyrova (Высшее образование в России)
The article presents the results of sociological survey: questioning of graduates of the professional educational organizations of Zelenodolsk town, analyzes the main reasons of youth migration from small towns to megalopolises. Basing on higher education institution practice the authors offer solutions of typical problems for many cities of Russia.